MOTIVASI DOSEN: Bekerja hingga Ibadah (Studi pada Dosen Program Studi Manajemen Universitas Islam Indonesia) - Putri Oktovita Sari; Robby Sandhi Dessyarti (Jurnal Ekonika : Jurnal Ekonomi Universitas Kadiri, 2019)
The objective of this research is to descripe lecturer’s motivation in work which is assessed by teaching and learning process. Lecturer’s motivation consists of intrinsic and extrinsic encouragement. Intrinsic encouragement is more directed at nonfinancial aspects (worship, pleasure). While extrinsic motivation is more directed at financial aspects (position). This research use qualitative approach with the number of respondents as much four lecturers of Management Department of Universitas Islam Indonesia. Sample is selected by purposive sampling. The sample is determined based on criteria determined by researcher. The results of this research indicate that the lecturers have different motivations in carrying out their profession. The motivation of a lecturer is more towards non-financial aspects, a job that is liked, work as a worship, work as a career and work as a pleasure that grows out of compulsion. This research also found evidence that financial will not always provide encouragement for someone. Motivation is very important because it is closely to the performance of the lecturer. Lecturers who have high motivation will exert their thoughts and energy to carry out their duties and responsibilities professionally. In other word, the lecturers’s motivation is able to encourage their performance.